Pelatihan Kewirausahaan Ekonomi Kreatif Karang Taruna Tanah Putih Kabupaten Rokan Hilir - Moenada, Meimunah S.; Riofita, Hendra (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
The objective of this dedication was to prepare the Youth of Karang Taruna Kecamatan Tanah Putih Kabupaten Rokan Hilir as spearhead of poverty eradication toward ability to increase creative economic effort for themselves, organization and the communities around them, to train them to do creative economic business toward converting used goods to be goods having sale value and to help them to build their own creative economic business. The methods applied were presentation, games, case study, question and answer and all methods were applie by using andragogy approach. The result showed that all trainees were enthusiastic to have their own business. It was proved by the plans to set up business they presented. Besides all trainees could concert used goods to be goods having sale value like wallet, tissue box, pencil box, rice box, egg box and bag.